Position of Collective Labor Agreement as a Company Autonomous Law: Industrial Relation Dispute Settlement Approach - Kadek Agus Sudiarawan; Putu Ade Harriesta Martana; Nyoman A. Martana; Bagus Hermanto (University of Udayana, 2019)
Collective Labor Agreement (CLA) is one of the main pillars that can be used in resolving disputes that occur in the company, However, there are problems concerning the implementation of CLA. The purpose of this research is to find and identify factors that can trigger disputes in the implementation of CLA, the probability of amendment of the CLA, identify the position of CLA in resolving Industrial Relation Disputes and find a mechanism of settlement in the implementation of the CLA. The research was carried out using empirical legal methods and analyzed using qualitative methods. The results are presented in a descriptive analysis report. The results of this research showed differences in interpretation, when unclear validity arrangements and adjustments of the new legislation happen were triggering disputes in the implementation of the CLA. Based on goodwill from the CLA parties, amendments could be made through negotiations in accordance with the mechanism stipulated in the Laws and Regulations. The position of CLA is an autonomous law that applies to the company and is an important element in preventing and resolving Industrial Relation Disputes. Finally, the settlement through bipartite, tripartite and Industrial Relation Court are the mechanism that can be taken for interest disputes.